Combating iodine and iron deficiencies through the double fortification of fish sauce, mixed fish sauce, and salt brine - Visith Chavasit (2018)
Two iodine and seven iron compounds were tested for use in the fortification of pure fish sauce, mixed fish sauce, and salt brine for cooking as a means to combat iodine and iron deficiencies. Ferrous sulfate, sodium iron ethylenediaminetetraacetic acid, ferric ammonium citrate, and ferrous lactate were combined with potassium iodide with no effect on sensory quality. Product shelf-life testing revealed that no iron or iodine losses occurred during a three-month storage period. Although the color of most products darkened, the color was not significantly different from that of nonfortified products after two to three months. Sensory home-use tests revealed that the fortified products were acceptable to highly acceptable, with only 1.2% to 8.2% of the dishes cooked using the fortified products being reported as discolored. The cost of fortification was minimal, at 0.13 to 2.73 baht per bottle (750 ml)(42 baht = US$1). Consequently, these products show a potential for inclusion in national programs for the prevention of micronutrient deficiencies in Asian countries where fish sauce and its products are routinely consumed.